Differential motor neuron involvement in progressive muscular atrophy: a comparative study with amyotrophic lateral sclerosis. Issue 5 (14th May 2014) - Riku, Yuichi; Atsuta, Naoki; Yoshida, Mari; Tatsumi, Shinsui; Iwasaki, Yasushi; Mimuro, Maya; Watanabe, Hirohisa; Ito, Mizuki; Senda, Jo; Nakamura, Ryoichi; Koike, Haruki; Sobue, Gen
Abstract : Objective: Progressive muscular atrophy (PMA) is a clinical diagnosis characterised by progressive lower motor neuron (LMN) symptoms/signs with sporadic adult onset. It is unclear whether PMA is simply a clinical phenotype of amyotrophic lateral sclerosis (ALS) in which upper motor neuron (UMN) signs are undetectable. To elucidate the clinicopathological features of patients with clinically diagnosed PMA, we studied consecutive autopsied cases. Design: Retrospective, observational. Setting: Autopsied patients. Participants: We compared clinicopathological profiles of clinically diagnosed PMA and ALS using 107 consecutive autopsied patients. For clinical analysis, 14 and 103 patients were included in clinical PMA and ALS groups, respectively. For neuropathological evaluation, 13 patients with clinical PMA and 29 patients with clinical ALS were included. Primary outcome measures: Clinical features, UMN and LMN degeneration, axonal density in the corticospinal tract (CST) and immunohistochemical profiles. Results: Clinically, no significant difference between the prognosis of clinical PMA and ALS groups was shown. Neuropathologically, 84.6% of patients with clinical PMA displayed UMN and LMN degeneration. In the remaining 15.4% of patients with clinical PMA, neuropathological parameters that we defined as UMN degeneration were all negative or in the normal range. In contrast, all patients with clinical ALS displayed a combination of UMN and LMN system degeneration. CST axon densities were diverse in the clinical PMA group, ranging from low values to the normal range, but consistently lower in the clinical ALS group. Immunohistochemically, 85% of patients with clinical PMA displayed 43-kDa TAR DNA-binding protein (TDP-43) pathology, while 15% displayed fused-in-sarcoma (FUS)-positive basophilic inclusion bodies. All of the patients with clinical ALS displayed TDP-43 pathology. Conclusions: PMA has three neuropathological background patterns. A combination of UMN and LMN degeneration with TDP-43 pathology, consistent with ALS, is the major pathological profile. The remaining patterns have LMN degeneration with TDP-43 pathology without UMN degeneration, or a combination of UMN and LMN degeneration with FUS-positive basophilic inclusion body disease.